2017
DOI: 10.1097/mao.0000000000001271
|View full text |Cite
|
Sign up to set email alerts
|

Older Individuals Meeting Medicare Cochlear Implant Candidacy Criteria in Noise but Not in Quiet: Are These Patients Improved by Surgery?

Abstract: All patients undergoing CI candidacy testing should be tested in both quiet and noise conditions. For those who qualify only in noise, our results demonstrate that cochlear implantation typically improves hearing both in quiet and noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…In light of improving outcomes and concerns about ceiling effects, the MSTB committee revised the sentence material recommendations in 2011, suggesting use of monosyllabic words in addition to AzBio Sentences (4) in quiet and noise and Bamford-Kowal-Bench Speech-in-Noise (BKB-SIN;(5)) test (6). Subsequent studies demonstrated the clinical value of these speech in noise measures for 1) approximating realistic listening environments, 2) assessing listeners’ complaints, 3) avoiding ceiling effects, 4) and evaluating pre- and postoperative performance in populations that may not struggle in quiet (710).…”
Section: Introductionmentioning
confidence: 99%
“…In light of improving outcomes and concerns about ceiling effects, the MSTB committee revised the sentence material recommendations in 2011, suggesting use of monosyllabic words in addition to AzBio Sentences (4) in quiet and noise and Bamford-Kowal-Bench Speech-in-Noise (BKB-SIN;(5)) test (6). Subsequent studies demonstrated the clinical value of these speech in noise measures for 1) approximating realistic listening environments, 2) assessing listeners’ complaints, 3) avoiding ceiling effects, 4) and evaluating pre- and postoperative performance in populations that may not struggle in quiet (710).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In addition, many researchers have specifically demonstrated the effectiveness of this treatment in Medicareeligible recipients, who typically include US citizens older than 65 years. 7,8 Such treatment is particularly important for Medicare beneficiaries because hearing loss has been associated with depression, social isolation, and a subjective decrease in wellbeing in elderly individuals. [9][10][11][12][13] Medicare indications for a cochlear implant have been in existence since 2005 and state the following: "The evidence is adequate to conclude that cochlear implantation is reasonable and necessary for treatment of bilateral pre-or postlinguistic, sensorineural, moderate to profound hearing loss in individuals who demonstrate limited benefit from amplification.…”
mentioning
confidence: 99%
“…20 Speech-in-noise measures more appropriately reflect real-world listening performance and appear to have a higher sensitivity for selecting appropriate CI candidates than SIQ. 6,10,16 When SIN testing was used, it was conditionally based on scores obtained in quiet; yet no clear performance marker for when to include SIN was identified. These results differ from those reported by Carlson et al, 21 wherein 68% of respondents reported that SIN testing is performed routinely.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, criteria for Medicare candidates 15 tend to be more stringent than the FDA criteria despite increasing criticism of their appropriateness for selecting adult candidates for CI. 6,9,16 The primary objective of this study was to investigate preoperative assessment methods used by audiologists to evaluate adult candidates for CI in the United States. Secondarily, we investigated clinical practice variables that might contribute to decision-making regarding assessment methods.…”
mentioning
confidence: 99%